Raw Deal - Irvin, John.; McGavin, Darren, 1922-2006.; Joe Regalbuto; Kathryn Harrold; Paul Shenar; Sam Wanamaker; Steven Hill; Arnold Schwarzenegger (USA De Laurentiis Entertainment Group, 1986)
Mark Kaminsky is kicked out of the FBI for his rough treatment of a suspect. He winds up as the sheriff of a small town in North Carolina. FBI Chief Harry Shannon, whose son has been killed by a mobster named Patrovina, enlists Kaminsky in a personal vendetta with a promise of reinstatement into the FBI if Patrovina is taken down. To accomplish this, Kaminsky must go undercover and join Patrovina's gang.
Mark Kaminsky is kicked out of the FBI for his rough treatment of a suspect. He winds up as the sheriff of a small town in North Carolina...
Luciano Vincenzoni
Languages : English, German, Spanish, Italian Subtitles : English, Turkish, Italian
Keywords: Action